1973
DOI: 10.2337/diab.22.7.499
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nicotinamide and Pyridine Nucleotides on Streptozotocin and Alloxan Induced Pancreatic B Cell Cytotoxicity

Abstract: Pancreas from mice treated with 500 ing. per kilogram of nicotinamide intraperitoneally fifteen minutes before 200 nig. per kilogram of streptozotocin intravenously showed mostly unaltered islet B cells after eight, eighteen or fortyeight hours. Mice pretreated with 1,500 mg. per kilogram of either NAD, NADP or NADPH intraperitoneally showed almost no B cell lesions at eight hours. At eighteen hours some B cell necrohiosis was observed but of lesser extent than that seen after streptozotocin alone at eight hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…142 and mode of action of streptozotocin has not been satisfactorily elucidated. In an attempt to explain the mechanism of action it has been suggested that diabetogenic activity of streptozotocin is mediated through its ability to lower pancreatic NAD+ concentrations significantly (Schein et al, 1967;Schein & Loftus, 1968;Schein & Bates, 1968;Junod et al, 1969;Ho & Hashim, 1972;Lazarus & Shapiro, 1973). This postulate is based on the observation that nicotinamide given either 10min before or up to 2h after streptozotocin prevents the development of diabetes (Dulin & Wyse, 1969a,b;Stauffacher et al, 1970;Lazarus & Shapiro, 1973).…”
mentioning
confidence: 99%
“…142 and mode of action of streptozotocin has not been satisfactorily elucidated. In an attempt to explain the mechanism of action it has been suggested that diabetogenic activity of streptozotocin is mediated through its ability to lower pancreatic NAD+ concentrations significantly (Schein et al, 1967;Schein & Loftus, 1968;Schein & Bates, 1968;Junod et al, 1969;Ho & Hashim, 1972;Lazarus & Shapiro, 1973). This postulate is based on the observation that nicotinamide given either 10min before or up to 2h after streptozotocin prevents the development of diabetes (Dulin & Wyse, 1969a,b;Stauffacher et al, 1970;Lazarus & Shapiro, 1973).…”
mentioning
confidence: 99%
“…However, recent work indicates that only when nicotinamide is administered before alloxan is the pancreatic islet protected, whereas nicotinamide administered up to 60 min after streptozotocin still has an antagonistic effect (27). In addition, the study of Lazarus and Shapiro has shown a failure of nicotinamide to prevent beta cell destruction by alloxan in the mouse (19). The temporal development of diabetes is similar with both alloxan and streptozotocin.…”
Section: Methodsmentioning
confidence: 95%
“…4) To explain the relative ineffectiveness of MNU as a diabetogenic agent, a comparative study of drug distribution of streptozotocin and MNU was performed. To avoid possible contamination of the pancreas and other (2,4) and is specific in its protective action against streptozotocin-induced diabetes (2,18 (19). They base their conclusion on the finding that intraperitoneally administered NAD only partially prevented streptozotocin-induced diabetes, as determined by histologic examination.…”
Section: Methodsmentioning
confidence: 99%
“…In characterizing the effects of streptozotocin, it was of interest to know whether nicotinamide or methylnicotinamide could protect against the streptozotocin-induced inhibition of proinsulin and total protein synthesis, just as they have been reported to protect the insulin release capability [17][18][19][20][21][22][23][24]. In one experiment, 10 mM nicotinamide or 4 mM methyl nicotinamide were included in the incubation medium with or without 2.2 mM streptozotocin.…”
Section: The Effects Of Streptozotocin Concentration and Time Of Expomentioning
confidence: 99%
“…Certainly, the administration of nicotinamide, a precursor of NAD in many tissues, protects against the diabetogenic effects of subsequently administered streptozotocin [17][18][19][20][21][22][23][24][25]. This protection may, however, unmask a long term oncogenic effect of the drug [26,27].…”
mentioning
confidence: 99%